The intellectual structure of the waste management field - Argoubi, Majdi; Jammeli, Haifa; Masri, Hatem (Annals of operations research, 2020)
Waste management is an important issue in the field of green logistics. It has consequently drawn the attention of the scientific community and has been extensively investigated over the past few years. Through an analysis of the existing waste management literature, we attempt in this paper to better understand past developments in this area as well as emerging trends and recent developments. Emphasis will be put mainly on Operations Research and Management Science techniques when dealing with waste management problems. To reach this target, we follow bibliometric-based methods, specifically Co-citation Analysis, Betweenness Centrality and Burst Detection combined with network visualization. After identifying the research papers published between 1990 and 2018 within the Thomson Reuters Web of Science database, a Co-citation network has been constructed. We propose an algorithm for modularity-based clustering in small networks that iteratively solves a sequence of Mixed Integer Non-linear Programming problems to maximize the modularity therefore providing a non-overlapping partition of the network. A display of the principal research areas and landmark articles that shape the intellectual structure of the waste management problems during the last 30 years is reported.